STRATEGI DAN UPAYA PENGELOLAAN SAMPAH BERBASIS TEKNOLOGI TEPAT GUNA DI DESA TAMANAYU, LUMAJANG - Sa'adah, Siti Malihatus; Alamsyah, Moch. Rega Nur; Firmansyah, Moch. Syafrijal; Ramadhiana, Feby Zulfa; Mubarok, Fajar Syarif; Muarif, M. Samsul; Muniroh, Siti Sa'adatul; Muyassaroh, Sitti; Nisa', Siti Jauharotun; Akbar, Moch. Bima; Rahayu, Hastanti Agustin (-, 2024)
Tamanayu is one of the villages that has problems in waste management. The low level of public awareness and the absence of a TPS make people still throw garbage carelessly. Therefore, it is needed a solution that can be used to reduce the number of landfills. The research is conducted to determine alternative solutions that are effective in waste management in Tamanayu village. The research method used is the CBPR (Community Based Participatory Research) method by observing and socializing the Tamanayu village community. Based on the results of observations, conducting socialization, counseling on waste management and providing periodic assistance in collaboration with Environmental Agency (DLH), and presentation about incinerator prototypes environmentally friendly waste (incinerator) are suitable alternative solutions for waste management in Tamanayu village. The community showed enthusiasm and positive response to the results of the socialization and presentation of the prototype of the incinerator, and agreed to achieve the results of the socialization provided. It is hoped that the community will be more active in playing a role in waste management at Tamanayu village in the future.